An Analytical Study of Buyers’ Behaviour Towards Automatic Fuel Pricing and Price Smoothing in India - Jain, Shikha; Kamble, Suraj Chandrakant (Prabandhan: Indian Journal of Management, 2021)
India is the third-largest country in fuel consumption and followed the Administered Pricing Policy for fixing the retail fuel prices. In June 2017, India moved to Automatic Fuel Pricing on a full scale, which enabled automatic, everyday adjustment of retail petrol and diesel prices in line with global prices. In an automatic or dynamic fuel pricing mechanism, the retail price is revised daily in response to changes in global prices. Automatic fuel pricing made the fixation of prices more transparent and logical. Since the fuel pricing plays a vital role in economic transactions and involvement of public consumption, the need for further penetration into this arena exists, and thus, this study was carried out. Smoothing techniques in statistics are used to cancel or reduce the effects of random variations in data, which is collected over a period of time. The current study investigated the impact of price smoothing on buyers’ behaviour and tried to find out the impact of automatic fuel pricing on buyers’ behaviour through the data collected from 124 respondents across the country using a standardized questionnaire. Statistical analysis tools such as cross tabulation, pie-charts, histogram, regression, and ANOVA were employed to analyze the data and test the hypotheses. The major results indicated that buyers were positive towards daily revision of prices and believed that daily price revision brought transparency in fuel price fixation and reduced fuel price speculation. In response to the pre-payment scheme, facts revealed that buyers were inclined towards the pre-payment scheme, and they would opt for this scheme if made available in the market and were ready to deposit a specified amount with a vendor. Mixed responses were obtained from the buyers when they were asked to opt for the scheme with some terms and conditions.